HISTORY THROUGH LITERATURE - Fear, Alan (SÉCULO XXI: Revista de Relações Internacionais - ESPM, 2023)
Abstract This article explores the similarities between historical narrative and historical fiction. History as it is traditionally interpreted and reported may or may not be entirely accurate or reliable, but is generally accepted as “history”. Historical fiction also shares these same properties and furthermore can give deeper insights into characters and events in a more engaging manner allowing the reader to connect and to relate more to these characters and events from the past than a history narrative would, thus forming a bridge between academic study and popular engagement with history. In this paper, I examine historiography and the historical novel and show through three examples that history can be studied and learned equally through reading a historical narrative or a historical-fictional account. Key words: history; historiography, historical novel,